Gradual solid-state redox-isomerism in the lanthanide series - Lukina, Daria A; Skatova, Alexandra A; Rumyantcev, Roman V; Demeshko, Serhiy V; Meyer, Franc; Fedushkin, Igor L (Dalton transactions : an international journal of inorganic chemistry, 2024)
Oxidation of [(Ar BIG -bian) 2− Yb 2+ (dme)] ( 1 ) (Ar BIG -bian = 1,2-bis[(2,6-dibenzhydryl-4-methylphenyl)imino]acenaphthene; dme = 1,2-dimethoxyethane) by 0.5 equivalent of Me 2 NC(S)S-S(S)CNMe 2 in dme at ambient temperature affords a mixture of two products, [(Ar BIG -bian) 2− Yb 3+ {SC(S)NMe 2 } 1− (dme)] and [(Ar BIG -bian) 1− Yb 2+ {SC(S)NMe 2 } 1− (dme)], which represent two redox-isomers ( 2a and 2b , respectively). Their ratio in solution depends on the solvent as well as on the temperature. In the solid state, a decrease of temperature (350 → 100 K) caused an electron transfer from the Yb 2+ ion to the Ar BIG -bian radical-anion in isomer 2b to afford isomer 2a . Accordingly, the ratio of isomers 2a and 2b changes from 1 : 1 (350 K) to 3 : 1 (100 K). In contrast, in the dimer [(dme)(dpp-bian) 1− Yb 2+ (μ-Cl) 2 Yb 3+ (dpp-bian) 2− (dme)] (dpp-bian = 1,2-bis[(2,6-diisopropylphenyl)imino]acenaphthene), which is the sole example of a lanthanide complex that reveals solid-state redox-isomerism (valence tautomerism) reported so far, the electron transfer from the Yb 2+ ion to the dpp-bian radical-anion takes place at around 150 K and is completed within a temperature interval of ca . 7 K. The dithiocarbamate derivative [(Ar BIG -bian)Yb{SC(S)NMe 2 }(dme)] ( 2 ) exhibits a unique gradual solid-state redox-isomerism that involves a temperature-induced reversible electron transfer between the metal and the ligand.